Inequality in early childhood neurodevelopment in six poor rural counties of China: a decomposition analysis - Cuihong Zhang; Chunxia Zhao; Xiangyu Liu; Qianwei Wei; Shusheng Luo; Sufang Guo; Jingxu Zhang; Xiaoli Wang; Robert W. Scherpbier (BMC, 2017)
Abstract Background Previous studies about inequality in children's health focused more on physical health than the neurodevelopment. In this study, we aimed to evaluate the inequality in early childhood neurodevelopment in poor rural China and explore the contributions of socioeconomic factors to the inequality. Method Information of 2120 children aged 0 to 35 months and their households in six poor rural counties of China was collected during July - September, 2013. Age and Stages Questionnaire-Chinese version, concentration index and decomposition analysis were used to assess the neurodevelopment of early childhood, measure its inequality and evaluate the contributions of socioeconomic factors to the inequality, respectively. Result The prevalence of suspected developmental delay in children under 35 months of age in six poor rural counties of China was nearly 40%, with the concentration index of −0.0877. Household economic status, caregivers' depressive symptoms, learning material and family support for learning were significantly associated with children's suspected developmental delay, and explained 34.1, 14.1, 8.9 and 7.0% of the inequality in early childhood neurodevelopment, respectively. Conclusion The early childhood neurodevelopment in the surveyed area is poor and unfair. Factors including household economic status, caregivers' depressive symptoms, learning material and family support for learning are significantly associated with children's suspected developmental delay and early developmental inequality. The results highlight the urgent need of monitoring child neurodevelopment in poor rural areas. Interventions targeting the caregivers' depressive symptoms, providing learning material and developmental appropriate stimulating activities may help improve early childhood neurodevelopment and reduce its inequality.